Optimalisasi Bank Sampah Berbasis Teknologi untuk Peningkatan Kesejahteraan Komunitas di Lombok Timur - Rizal Maulana; Siti Nurhayati; Agus Firman (UNITY: Journal of Community Service, 2026)
Household waste management in East Lombok shows a continuous increase in unmanaged inorganic waste. Waste banks function as community empowerment instruments, yet limited transaction recording systems, low transparency, and restricted access to information constrain their impact on community welfare. This community service program aims to optimize waste bank performance through the implementation of technology based on a web system and simple applications to support operational management, transaction recording, and monitoring of waste economic value. The implementation method includes baseline assessment, digital system training, operational assistance, and performance evaluation using economic and participation indicators. The results indicate improved operational efficiency, higher transaction data accuracy, and an increase in average member income. Community participation also rises due to easier information access and transparent management. Technology based waste bank optimization strengthens governance, promotes economic independence, and supports sustainable improvement of community welfare in East Lombok.